Fabrication, phase, microstructure and electrical properties of BNT-doped (Sr,La)TiO3 ceramics - Eaksuwanchai,P. (Korean Physical Society, 2015)
This research studied the effects of Bi0.5Na0.5TiO3 (BNT) doping on the phase, density, microstructure and electrical properties of (Sr,La)TiO3 (SLTO) ceramics. Separately calcined SLTO and BNT powders were mixed together to form (1-x)SLTO-xBNT (where x = 0, 0.01, 0.03, 0.05 and 0.07 mol fraction) compounds that were pressed into pellets and then sintered at 1500 °C for 3 h under ambient atmosphere. The relative bulk densities of all the ceramics were greater than 95% their theoretical values which were confirmed by their nearly zero-porosity microstructure. X-ray diffraction patterns indicated complete solid solutions with a cubic structure and a slight lattice contraction when BNT was added. The electrical conductivity was found to decrease with BNT addition, suggesting a reduced number of mobile charges. The dielectric constant also showed limited polarization due to defect dipoles formed by aliovalent ionic substitution of BNT. Further optimization in terms of composition and defect chemistry could lead to a compound suitable for thermoelectric applications. © 2014 The Korean Physical Society.